Design and construction of automated equipment for separating mixtures - Martinez Baquero, Javier Eduardo (Visión electrónica, 2014)
There are various forms of environmental pollution, one of which is caused by oily mixtures which are particularly discharged into water sources from economic activities such as washing vehicles, service stations, and others. This article research shows a way to mitigate these polluting effects through the design and construction of an automated equipment that performs the separation of a mixture of water-oil. The separation of the oil mixture is carried out in a corrugated plate interceptor (CPI), and accompanied by a Programmable Logic Controller (PLC) S7 1200, through which the user is allowed to perform the process efficiently, thanks to high percentage of separation has been achieved with respect to the initial mixture. Then, was divided into three methodological steps , first the CPI separator built, setting turn the variables of interest, second was designed and implemented the Automation and third results were validated by testing. Three variables were defined; level, the most important in the system, also temperature and flow, for each of them has been implemented appropriate instrumentation for data collection subsequently entering the PLC. The main result is that the process is efficient as it manages to recover more than 90% of the water present in the initial oily fluid, this evidenced by the implemented instrumentation , allowing reuse and subsequent saving precious liquid.